2023
DOI: 10.1021/acs.nanolett.3c00988
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Hybrid Inner Ear Organoid with Enhanced Maturity

Abstract: Inner ear organoids (IEOs) are 3D structures grown in vitro, which can mimic the complex cellular structure and function of the inner ear. IEOs are potential solutions to problems related to inner ear development, disease modeling, and drug delivery. However, current approaches in generating IEOs using chemical factors have a few limitations, resulting in unpredictable outcomes. In this study, we propose the use of nanomaterial-based approaches, specifically by using graphene oxide (GO). GO’s unique properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This increase in the expression of Smad3 and Tgfb1 genes is likely associated with the presence of graphene, which forms the surface on which the cells are cultured. Other studies, including those by Shim NY et al [95], Yang Y et al [96] and Park S et al [97], have demonstrated that the addition of graphene, a biocompatible material that serves as an excellent substrate for culturing stem cells, influences cell proliferation and Smad3-regulated pathways. Graphene addition also enhances interactions between cells and the extracellular matrix and intercellular junctions through signaling pathways involving TGFB1.…”
Section: The Assessment Of the L-929 Cell Line After Exposure To The ...mentioning
confidence: 99%
“…This increase in the expression of Smad3 and Tgfb1 genes is likely associated with the presence of graphene, which forms the surface on which the cells are cultured. Other studies, including those by Shim NY et al [95], Yang Y et al [96] and Park S et al [97], have demonstrated that the addition of graphene, a biocompatible material that serves as an excellent substrate for culturing stem cells, influences cell proliferation and Smad3-regulated pathways. Graphene addition also enhances interactions between cells and the extracellular matrix and intercellular junctions through signaling pathways involving TGFB1.…”
Section: The Assessment Of the L-929 Cell Line After Exposure To The ...mentioning
confidence: 99%
“…These nanocomposites were internalized by cancer cells expressing folate receptors and demonstrated high cytotoxicity when subjected to NIR laser rays [245]. promote cell-extracellular matrix interactions and cell-cell gap junctions, potential applications for drug testing [247] GO U87, U251 GSCs and primary GSCs GO could promote differentiation and reduce malignancy in GSCs via an unanticipated epigenetic mechanism [244] Graphene oxide (GO) flakes Human Glioblastoma GO flakes translocated deeply into the spheroids [243] Gold-graphene hybrid nanomaterial (Au@GO) co-culture spheroids of HeLa/Ovarian cancer and HeLa/human umbilical vein endothelial cell (HUVEC)…”
Section: Frontiers In Pancreatic Cancermentioning
confidence: 99%